Obesity and associated factors among high school adolescent students in Bahir Dar town, North West Ethiopia: A cross-sectional study. (December 2022) - Hunegnaw, Woldeamilak Adamu; Ferede, Addisu Gasheneit; Tekalign, Tiwabwork; Asres, Abiyot Wolie
Objective: The aim of this study was to assess the magnitude and associated factors of obesity among high school adolescent students in Bahir Dar, Ethiopia. Methods: An institution-based cross-sectional study was conducted from 10 September 2019 to 10 October 2019 in Bahir Dar town. A total of 1018 students were enrolled using a multistage sampling procedure. Epidata version 3.1 was used for data entry, and SPSS version 24 was used for data analysis. A bivariable and multivariable logistic regression analysis was performed. Results: The magnitude of obesity among high school adolescents was 8.3%. Attending a private school (adjusted odds ratio = 6.52; 95% confidence interval: 3.13, 13.59), not participating in moderate- to vigorous-intensity activities (AOR = 3.08; 95% confidence interval: 1.44, 6.64), coming from a wealthy family (adjusted odds ratio = 7.03; 95% CI: 2.16, 22.89), and snacking frequency (adjusted odds ratio = 9.64; 95% confidence Interval: 4.79, 19.39) were all associated with obesity. Conclusions: Obesity was prevalent among students in private schools and wealthy families in the research area. Family size, household wealth, participation in moderate-to-striving activities, and snacking frequency were all found to be significant factors of obesity.